Vat polymerization-based 3D printing of nanocomposites: A mini review - Li, Yuewei; Wang, Wanyue; Wu, Fuhang; Kankala, Ranjith Kumar (Frontiers in Materials, 2023)
Vat polymerization, the earliest and most established 3D printing technology, offers abundant advantages of high-precision fabrication and rapid printing speed, among others. This technology is often applied to fabricated objects with complex and delicate structures, which are of specific interest in numerous fields. However, it suffers from poor mechanical properties of the resultant printed parts due to layer-by-layer manufacturing patterns and the absence of functionality, restricting the broader application of printed objects. Integrating nanomaterials with vat polymerization-based 3D printing endows the creation of products with enhanced properties and unprecedented functional adjunction with flexible designs. Giving a brief description of 3D printing technology, this review illustrates the principles and characteristics of vat polymerization technology. In this mini-review, we emphasize recent advances in nanocomposite fabricated using vat polymerization, predominantly focusing on creating nanocomposites with enhanced mechanical, thermal properties, and electrical conductivity. Finally, we summarize the article with the challenges being faced and future perspectives of nanocomposites fabricated from vat polymerization.